Research of Scalability of the Belt-Type Sensor Networks - 徐志广 朱磊基 施玉松 姜华 (Shanghai jiao tong da xue xue bao, 2012)
For the large-scale application requirements of the belt-type networks, the mathematical modeling as well as quantitative analysis for the scalability of the network based on average path length is completed in this paper, and the theorem for the scale scalability of the belt-type networks is derived. The theorem provides a calculation formula for the upper limit of node scale theory of the belt-type networks and a calculation formula for the upper limit of single node load theory.